Influence of smoking habits on change in carbon monoxide transfer factor over 10 years in middle aged men. Issue 2 (February 1993) - Watson, A; Joyce, H; Hopper, L; Pride, N B
Abstract : BACKGROUND: Emphysema is associated with a reduction in carbon monoxide transfer coefficient (TLCO/VA), but little is known about the evolution of changes in TLCO/VA in middle aged smokers at risk of developing chronic airflow obstruction. METHODS: TLCO/VA (single breath method) was measured on two occasions 10 years apart in 122 middle aged men. RESULTS: Initially TLCO/VA averaged 97% predicted in never smokers (n = 42, mean age 37.2 years), 99% predicted in ex-smokers (n = 21, mean age 41.9 years), and 85% predicted in those who smoked over 15 cigarettes a day (n = 42, mean age 42.0 years). Mean rates of decrease in TLCO/VA over 10 years, however, were similar in the three groups, so that differences between smokers and non-smokers did not increase during the 10 years. Seventeen men (mean age 40.9 years) who initially were smokers became sustained ex-smokers within two years of the first measurement; in these men mean absolute values of TLCO/VA rose, averaging 89% predicted at the first assessment but 102% predicted 10 years later. CONCLUSION: By the age of about 40 years TLCO/VA was lower in smokers than in never smokers but this difference did not increase over the following 10 years. Sustained ex-smokers had values similar to those of never smokers even when TLCO/VA was known to have been reduced while they were smoking. Changes in TLCO/VA associated with stopping smoking were considerably larger than could be explained by carbon monoxide back pressure, indicating that mechanisms other than irreversible increase in the size of terminal air spaces underlie the lower values in smokers. To detect emphysema in smokers it is necessary to use reference equations that take account of current smoking.